Peran Mediasi Kepuasan Pelanggan pada pengaruh kualitas pelayanan terhadap kinerja karyawan di Politeknik Pelayaran Surabaya - Elise Dwi Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of service quality on employee performance which is mediated by customer satisfaction at the Surabaya Shipping Polytechnic. This type of research is quantitative research. The population used in this research were all employees at the Surabaya Shipping Polytechnic. The sampling technique used was the purposive sampling technique. The sample in this research was 100 respondents. The data collection technique used was a questionnaire. The data analysis technique used is simple regression analysis. The research results show that service quality influences employee performance at the Surabaya Shipping Polytechnic. This means that the higher the quality of service, the higher the employee performance; There is an influence of customer satisfaction on employee performance at the Surabaya Shipping Polytechnic. This means that the higher the customer satisfaction, the higher the employee performance; Customer satisfaction mediates the influence of service quality on employee performance at the Surabaya Shipping Polytechnic. This means that customer satisfaction can strengthen the impact of service quality on employee performance at the Surabaya Shipping Polytechnic. Keywords: customer satisfaction, employee performance, service quality.